The Role of Corporate Governance and Financial Performance on Financial Distress - Tyfani Heriyanto; Maria Septijantini Alie; Yudhinanto CN; Desmon Desmon; Eka Travilta Oktaria; Megasari Megasari; Umar Bakti (Journal of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study examines the influence of good corporate governance—comprising institutional ownership, the board of directors, the board of commissioners, independent commissioners, and the audit committee—on financial distress, with financial performance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024. Research Methodology: A quantitative approach using secondary data from the financial reports of 15 manufacturing companies over five years (75 samples) was applied. Purposive sampling was used, and data were analyzed to test both the direct and indirect effects of corporate governance components on financial distress through financial performance. Results: The findings show that all corporate governance components simultaneously affect financial distress. Specifically, institutional ownership, the board of commissioners, and the audit committee negatively and significantly influence financial distress, both directly and via financial performance. Meanwhile, the board of directors and independent commissioners positively and significantly affect financial distress, both directly and through financial performance. Conclusions: Good corporate governance plays a significant role in shaping financial distress, and financial performance acts as an important mediating mechanism. Certain governance elements can either mitigate or exacerbate financial distress depending on their influence. Limitations: This study is limited to manufacturing companies listed on the Indonesia Stock Exchange and focuses on selected governance indicators, excluding external economic or industry-specific factors. Contribution: The study provides empirical evidence on the role of corporate governance in financial distress and highlights the mediating function of financial performance, offering practical guidance for managers and investors to improve governance structures and enhance firm stability and performance.